DAMPAK DAN PERTANGGUNGJAWABAN TINDAK PIDANA ASIMILASI COVID-19 TERHADAP MASYARAKAT SEKITAR - Romadhan, Moh. Lubsi Tuqo (Universitas Muhammadiyah Ponorogo, 2020)
The Narapida assimilation program carried out by the central government, especially the policies issued by the Ministry of Law and Human Rights (KEMENKUMHAM) has so far become a pro and contra polemic among and the views of the community itself, politicians, legal experts, as well as the views of academics who are actively involved in paying attention to problems. the. Instead, this was done so that it could break the chain of spreading Covid-19 in Indonesia. However, this policy actually caused so many new problems and unrest in the society itself. We know that until now there have been many criminal acts committed by the assimilation of prisoners, either by stealing, committing mischief, and even killing. Until recently, the case of the murder and rape of a mother and child named angga, who came from Birem Bayeun, East Aceh. And again none other than the perpetrator of this crime is a prisoner who is following the Covid-19 Assimilation program in East Aceh.